Essentials of Point-of-Care Ultrasound Coding and Billing at the Neonatal Intensive Care Unit Setting in the United States - Chan, Belinda; Mnyavanu, Natalie; Bhombal, Shazia; Fraga, María V.; Groves, Alan M.; Marshall, Stephanie; Mukthapuram, Shanmukha; Singh, Yogen; on behalf of the members of National Neonatal POCUS Collaborative (American Journal of Perinatology, 2024)
Point-of-care ultrasound (POCUS) has increasingly been used by neonatal providers in neonatal intensive care units in the United States. However, there is a lack of literature addressing the complexities of POCUS coding and billing practices in the United States. This article describes the coding terminology and billing process especially those relevant to neonatal POCUS. We elucidate considerations for neonatal POCUS billing framework and workflow integration. Directions on image storage and supporting documentation to facilitate efficient reimbursement, compliance with billing regulations, and appeal to insurance claim denial are discussed.Key Points
Keywords: neonate; point-of-care ultrasound; billing; reimbursement; ICD codes; CPT Codes